Nanocomposite containing amorphous calcium phosphate nanoparticles for caries inhibition - Xu, Hockin H.K.; Moreau, Jennifer L.; Sun, Limin; Chow, Laurence C. (Dental materials, 2011)
The main challenges facing composite restorations are secondary caries and bulk fracture. The objectives of this study were to synthesize novel nanoparticles of amorphous calcium phosphate (NACP), develop NACP nanocomposite with calcium (Ca) and phosphate (PO 4) ion release to combat caries, and investigate the effects of NACP filler level and glass co-filler reinforcement on composite properties. NACP (diameter = 116 nm) were synthesized via a spray-drying technique for the first time. Since the local plaque pH in the oral cavity can decrease to 5 or 4, photo-activated composites were tested with immersion in solutions of pH 7, 5.5, and 4. Composite mechanical properties as well as Ca and PO 4 ion release were measured vs. pH and filler level. Increasing the NACP filler level increased the ion release. At 28 d and pH 4, the Ca release was (4.66 ± 0.05) mmol/L at 20% NACP, much higher than (0.33 ± 0.08) at 10% NACP ( p < 0.05). Decreasing the pH increased the ion release. At 20% NACP, the PO 4 release at 28 d was (1.84 ± 0.12) mmol/L at pH 4, higher than (0.59 ± 0.08) at pH 5.5, and (0.12 ± 0.01) at pH 7 ( p < 0.05). However, pH had little effect on composite mechanical properties. Flexural strength at 15% NACP was (96 ± 13) MPa at pH 4, similar to (89 ± 13) MPa at pH 5.5, and (89 ± 19) MPa at pH 7 ( p > 0.1). The new NACP nanocomposites had strengths that were 2-fold those of previous calcium phosphate composites and resin-modified glass ionomer control. NACP composites were developed for the first time. Their strengths matched or exceeded a commercial composite with little ion release, and were 2-fold those of previous Ca–PO 4 composites. The nanocomposite was “smart” as it greatly increased the ion release at a cariogenic pH 4, when these ions would be most needed to inhibit caries. Hence, the new NACP composite may be promising for stress-bearing and caries-inhibiting restorations.